KEMAMPUAN MENINGKATKAN PERTUMBUHAN LABA PERBANKAN DILIHAT DARI PENGARUH KESEHATAN KEUANGAN BANK - Hendratni, Tyahya Whisnu; Nawasiah, Nana; Indriati, Trisnani (Jurnal Riset Manajemen dan Bisnis (JRMB) Fakultas Ekonomi UNIAT, 2018)
The purpose of this study was to determine the effect of the ratio of Capital Adequacy Ratio (CAR), Loan to Deposite Ratio (LDR), Operational Income Operating Costs (BOPO) to Bank Profit Growth both partially and simultaneously at publicly traded bank companies in the Indonesia Stock Exchange (IDX ) period 2012 - 2016. The sample of this study is Commercial Banks in Indonesia which are listed on the Indonesia Stock Exchange (IDX) for the period of 2012 up to 2016 totaling 14 banks. This study uses quantitative data obtained from the Indonesia Stock Exchange with a method using multiple linear regression analysis. The results of the study show that simultaneously the CAR, BOPO, LDR variables affect earnings growth by 79% and the remaining 21% are influenced by other factors outside this research. Partially BOPO has a positive and significant effect on profit growth. While the CAR and LDR variables show that the results have no positive and insignificant effect on profit growth. Keywords: Profit Growth, CAR, BOPO, LDR